Iron-Catalyzed Direct Transformation of Benzylic Amines into Carbonyl Compounds in Water - Minakawa, Maki; Sasaki, Takashi (Synlett, 2019)
Fe-catalyzed direct transformation of benzylic amines into carbonyl compounds was performed in H2O. The reaction of benzylic amines with formaldehyde in the presence of FeCl3·6H2O in H2O afforded the corresponding carbonyl compounds (80 °C to reflux conditions; 14 examples, up to 94% yield). O18-labeling experiments indicated that the O atom in the generated carbonyl is derived from H2O.
Keywords: direct transformation; benzylic amines; carbonyl compounds; iron catalysis; formaldehyde